﻿Antecedents and consequence of patients' satisfaction with pharmaceutical service in hospitals: A multidimensional approach - Prasojo Pribadi; Riska; Susi Ari Kristina; Suci Paramitasari Syahlani; Satibi (Pensoft Publishers, 2023)
Measuring patient satisfaction and trust across various dimensions poses a challenge in the economic dynamics and service business development. Therefore, this study aims to analyze determinant factors of patient satisfaction and their impact on pharmacy trust. The investigation was carried out using a cross-sectional survey method with purposive sampling, and the questionnaire was designed based on a scientific literature review. The valid data obtained from 301 respondents were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that the greatest antecedent to patient satisfaction was drug efficacy, followed by drug education, personnel quality, and financial-health coverage (all significant at p < 0.05). Patient satisfaction positively influenced trust in the pharmacy (p < 0.05). However, the physical aspect, procedures-service promptness, medication supply, and social responsibility did not affect patient satisfaction. These results suggest that the process and outcome elements of pharmacy service are critical factors in relationships between patients and pharmacies.